Stunting prevention through posyandu in Margaasih - Ikrimah, Awalia Latifa Mayda; Rahmawati, Aulia; Putri, Farikha Diah Andini Hernowo (Universitas Pendidikan Indonesia, 2024)
There is still a stunting rate in Margaasih Village, so the village community is trying to reduce this rate with ongoing programs. The Posyandu program, one of the village health service programs running every month, seeks to reduce stunting rates. A team of Universitas Pendidikan Indonesia students conducted community service in Margaasih Village to help reduce stunting rates. One of the activities carried out by the service team is assisting ongoing village programs, namely the Posyandu program, counseling, and providing additional food. The team also implemented the program based on the results of surveys and problem identification carried out in Margaasih Village and assisted with PPosyandu activities in Margaasih Village, as well as providing additional food from processed catfish to help reduce stunting rates. The team also held counseling regarding complementary foods for breast milk with participant mothers who still have children aged infants to toddlers. It is hoped that this counseling can provide mothers with an understanding of what food preparations are suitable for babies and help reduce stunting rates.